Development and validation of a novel scoring system integrating MIBG scintigraphy and SPECT imaging for differentiating Parkinson’s disease - Yin, Pei; Wang, Yong; Jia, Lizhuo; Hao, Tiancheng; Gao, Yufei; Wu, Siqi; Wu, Jiangmeng; Wang, Danning (Frontiers in Neurology, 2025)
BackgroundEarly and accurate differentiation of Parkinson’s disease (PD) from other parkinsonian syndromes (PS) is crucial for appropriate management and prognostication. This study aimed to develop and evaluate a diagnostic model and a simplified scoring system combining clinical features, with parameters from cardiac ¹³¹I-MIBG scintigraphy, including planar-derived quantitative data (H/M ratio, clearance rate) and qualitative SPECT findings (uptake uniformity).MethodsThis retrospective study included 102 patients clinically diagnosed with PD and 71 patients with PS, based on their final diagnostic classification after follow-up. Data on demographic characteristics, clinical features, MIBG scintigraphy (15-min and 4-h heart-to-mediastinum (H/M) ratios, 4-h clearance rate), and SPECT findings (categorized as no uptake, uniform, or non-uniform) were collected. Patients with missing SPECT data were excluded. Univariate analyses were performed, and variables with p < 0.1 were included in a multivariate logistic regression model using backward selection. A simplified scoring system was derived from the logistic model. Receiver operating characteristic (ROC) curve analysis was used to assess diagnostic performance.ResultsThe final logistic regression model identified 4-h H/M ratio (OR 0.109, 95% CI 0.033–0.358), 4-h clearance rate (OR 4.500, 95% CI 1.030–19.651), and SPECT findings as significant predictors of PD. The logistic model achieved an area under the ROC curve (AUC) of 0.810 (95% CI 0.744–0.876), with a sensitivity of 81.4% and specificity of 70.4%. A derived combined score (ranging from 3 to 9 points) demonstrated an AUC of 0.800 (95% CI 0.736–0.864), with a sensitivity of 78.4% and specificity of 70.4% at a cutoff of 5 points.ConclusionA combination of MIBG scintigraphy parameters and SPECT imaging provides good diagnostic accuracy for differentiating PD from PS. The developed logistic regression model and the simplified scoring system offer promising tools for clinical practice, potentially improving diagnostic precision. Further prospective validation in larger, diverse cohorts is warranted.